Note on Higher-Order Statistics for the Pruned-State-Space of nonlinear DSGE models - Willi Mutschler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This note shows how to derive unconditional moments, cumulants and polyspectra of order higher than two for the pruned state-space of nonlinear DSGE models. Useful Matrix tools and computational aspects are also discussed.
Keywords: C10; C51; E10; 330